Interprovincial differences in the endowment and utilization in labour force by educational attainment in Indonesia's post-crisis economy - Mitsuhiko Kataoka (European Regional Science Association (ERSA), 2015)
The labour endowment and utilization across sub-national regions differ by educational attainment. Generally, the high-income developed regions are richly endowed with the highly educated that enjoys greater employment stability. The reverse may be true for the lower-income developing regions. The educational expansion affects educational endowment in labour force across sub-national regions and region-specific shocks and minimum wage regulations affect its utilization. We comprehensively explore the factors contributing to interregional inequalities in the labour endowment and utilization by educational attainment in the Indonesia?s post-crisis economy, introducing a variable of the employment with j educational attainment per capita (where j consists of five different levels of educational attainment) and employing Cheng and Li?s (2006) additive inequality decomposition method. Further, we employ Shorrocks? (1980) one-stage Theil decomposition method to measure the factors contributing to overall inequality in employment rate, which is the divergence between the employment rate in a nation and employment rates with j education attainment in province i. We find that the industrial structures and business functions seem to vary more widely from province to province than the other characteristics, such as demographic structures and labour market efficiency, do. The interprovincial differences in labour market efficiencies tend to be greater for the highly educated groups than the less educated. This is affected by several factors: no universal social security system, province-specific compositions of formal/informal sectors, and different minimum-wage provisions across provinces. Moreover, the interprovincial inequities in employment rates with the junior secondary education attainment have the most significant influences among all education groups. The recent increase in the corresponding labour force share could make this a crucial issue for the country. Consequently, policies for improving the efficiency in the corresponding labour market must be implemented. Cheng, Y.-S. and S.-K. Li. (2006) ?Income inequality and efficiency: A decomposition approach and applications to China?, Economics Letters 91 (1): 8?14. Shorrocks, A.F. (1980) ?The class of additively decomposable inequality measures?, Econometrica, 48 (3): 613?25.
Keywords: R11; R23; 330; decomposition analysis; interregional inequality; labor force